Brazilian climate normals for 1981–2010 - Diniz, Francisco de Assis; Ramos, Andrea Malheiros; Rebello, Expedito Ronald Gomes (Pesquisa Agropecuaria Brasileira, 2018)
In the last decades, especially since 2000, the natural vulnerability of Earth’s climate system has been a cause of great concern as to the status of global climate change due to the interference of natural and/or anthropic activities. Instituto Nacional de Meteorologia (Inmet), the government body officially responsible for monitoring weather and climate in Brazil, and also a member of the World Meteorological Organization (WMO), is proud to release the new edition of the climate normals for the period of 1981–2010. The new edition aims to analyze and register the climate changes that occurred during the two decades following the previous edition of 1961–1990. For that purpose, Inmet created a working group to prepare and edit these normals, as a basis of knowledge for different spheres of meteorology, aiming to strengthen the study and research of climate variability, as well as the Paris Agreement, which limits global warming to 1.5°C above pre-industrial levels. Finally, the publication intends to offer guidance, information, and assistance to the communities of climate sciences, agribusiness, and public and private institutions, both national and international. Overall, activities related to climate have expanded in practically every sphere of human life, especially in the fields of science and public policies.